Variables predicting ritualization of the Spring Festival among Chinese Thai youth in Hat Yai - Krueaphat, Kittinan; Laeheem, Kasetchai (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2023)
This study examined variables predicting ritualization of the Spring Festival among Chinese Thai youth in Hat Yai and created a prediction equation for the ritualization. The data were collected from 160 subjects who were selected using purposive sampling and data were analyzed using the R program to calculate Pearson’s product moment correlation coefficients and multiple linear correlation coefficients. The results of the study revealed seven predictors of ritualization of the Spring Festival among Chinese Thai youth in Hat Yai with predictability at a significance level of .001. Four predictors were found to have positive relationships with ritualization: family (X1), economy (X4), new media (X5), and governmental policy (X6). Governmental policy (X6) had the highest level of relationship, and family (X1) was the lowest.